The Effect of Squat Jump and Split Squat Jump Plyometric Training on Leg Power in Soccer Athletes - Aditya Eka Candra; Komarudin; Alen Rismayadi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
The purpose of this study was to determine the Effect of Squat Jump and Split Squat Jump Plyometric Exercises on the Leg Power of Football Athletes, with the research design applied in this study was "two groups pretest-posttest design". Group I was given squat jump treatment and group II was given split squat jump treatment. The location of this study was carried out at Al-Ma'soem High School, JL. Raya Cipacing No. 22, Jatinangor District, Sumedang Regency, West Java. The population in this study amounted to 20 people who were divided into two groups that would be given squat jump and split squat jump training actions. Samples were taken using a total sampling technique, where all populations would be samples in this study. The instrument used in this study was a vertical Jump test instrument, the test serves to measure individual leg muscle power. The test was carried out during the pretest and after being given posttest treatment. This data was processed using SPSS 22. The results of this study Sig from the squat jump and split squat jump groups was 0.000 which means less than 0.05. Furthermore, the squat jump group demonstrated a greater improvement compared to the split squat jump group. These findings indicate that both plyometric training methods are effective in enhancing lower-limb explosive power. In conclusion, squat jump and split squat jump exercises can be implemented as effective training strategies to improve leg muscle power in football athletes, providing valuable insights for coaches in optimizing training programs.